2019
DOI: 10.1177/1548512919860595
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainty and risk in an expeditionary military logistics network

Abstract: Uncertainty is rampant in military expeditionary operations spanning high-intensity combat to humanitarian operations. These missions require rapid planning and decision-support tools to address the logistical challenges involved in providing support in often austere environments. The US Army’s adoption of an enterprise resource planning system provides an opportunity to develop automated decision-support tools and other analytical models designed to take advantage of newly available logistical data. This rese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Accounting for this extra variation is an important feature for models pertaining to deployed military environments, where there are high levels of uncertainty. McConnell et al (2018) also observed overdispersion in logistical requisitions in deployed military environments. The literature notes this phenomenon in other applications as well, including arrivals at emergency rooms and call centers (Kim and Whitt 2014;Kim et al 2015;Whitt and Zhang 2015;Liu et al 2018).…”
Section: Arrival Processmentioning
confidence: 83%
See 1 more Smart Citation
“…Accounting for this extra variation is an important feature for models pertaining to deployed military environments, where there are high levels of uncertainty. McConnell et al (2018) also observed overdispersion in logistical requisitions in deployed military environments. The literature notes this phenomenon in other applications as well, including arrivals at emergency rooms and call centers (Kim and Whitt 2014;Kim et al 2015;Whitt and Zhang 2015;Liu et al 2018).…”
Section: Arrival Processmentioning
confidence: 83%
“…For a particular scenario, these quantities are fixed across the time horizon, resulting in a constant average arrival rate. We assume a fixed task organization and operational mission set over the time horizon; this was required based on the fidelity of the field artillery-specific data but is not a limiting assumption in general (indeed, future stud-ies should explicitly explore scenario-specific mission timelines; see McConnell et al 2018). For each parameter combination, the choice of echelon and maximum part volume results in a constant sample average arrival rate (e.g., 11.5 orders per day for three mechanized artillery battalions).…”
Section: Data Usedmentioning
confidence: 99%
“…Work [11] considers the issue of improving the reliability of logistics by the forces of the military logistics system. Two deception strategies are considered: the inclusion of empty convoys on routes and the spread of misinformation about the route.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Timely logistics support to military units in operations. McConnel (2018) conducted an extensive study on the problem of dropping equipment readiness due to distribution problems during military operations. The stochastic nature of the requirements for logistics support and varying service response led him to the use of queueing theory.…”
Section: Examples Of Military Applications Of Queueing Theorymentioning
confidence: 99%